NUMERACY AND ON-THE-JOB PERFORMANCE: EVIDENCE FROM LOAN OFFICERS - Martin Brown; Karolin Kirschenmann; Thomas Spycher (Economic Inquiry, 2020)
We examine how the numeracy level of employees influences their on-the-job performance. Based on an administrative dataset of a retail bank we relate the performance of loan officers in a standardized math test to the accuracy of their credit assessments of small business borrowers. We find that loan officers with a high level of numeracy are more accurate in assessing the credit risk of borrowers. The effect is most pronounced during the precrisis credit boom period when it is arguably more difficult to pick out risky borrowers. (JEL G21, J24)
Keywords: 330